EPISODE, MITEME, DAN OPOSISI BINER DALAM NOVEL LELAKI HARIMAU KARYA EKA KURNIAWAN - Dwi Yulianti Rahayu; Nabilah, Nisrina Rona; Pauji , Dicky Rachmat (Universitas Hamzanwadi, 2026)
This study aims to examine the narrative structure of Lelaki Harimau by Eka Kurniawan, focusing on the division of episodes, mythemes, and binary oppositions among characters. The main focus of this research is the application of Claude Lévi-Strauss’s structuralism to analyze the supernatural mythological element of the white tiger inhabiting the human body and its relationship to the social and cultural realities depicted in the novel. The study employs a descriptive qualitative approach using library research techniques, including close reading, data documentation, and interpretation based on episodes, mythemes, and binary oppositions. The findings indicate that the novel is structured into several episodes that portray Margio’s journey from the emergence of the white tiger to his process of redemption. Each episode contains interconnected mythemes and patterns of binary opposition, forming a structure of resistance against injustice and the social pressures experienced by the protagonist. The white tiger symbol functions as a mythological figure representing resistance, inner strength, and an inherited moral burden.